2022
DOI: 10.26618/jed.v7i1.6111
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of Pancasila Values Through School Cultivation During the Covid-19 Pandemic

Abstract: Internalization of Pancasila values must be given to students. Teachers need to find creative, innovative, inspirational, and contextual ways to cultivate Pancasila values in schools. This study aims to describe the results of best practices that have been carried out by teachers in cultivating Pancasila values during the Covid-19 pandemic. This research is a descriptive qualitative research. Data was collected by means of document studies, literature studies, observations, interviews, and documentation. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Strategi digunakan antara lain penugasan, pengarahan, pembiasaan, panutan dan pengkondisian lingkungan akan melekat pada diri anak melalui pengamatan dan melakukan secara nyata (Cinantya et al, 2019). Apalagi sejak masa pandemi pemulihan pembelajaran karakter akan menjadi satu sisi prioritas dengan rancangan media yang diciptakan guru harus yang inovatif dan kreativitas tinggi (Harnanto, 2022). Guru sebagai salah satu hal yang harus membentuk karakter siswa tidak memiliki nilai-nilai dasar itu harus digunakan dalam konteks karakter multikultural pada peserta didik upaya guru untuk melatih kemandirian anak dimaksimalkan (Banamtuan & Natonis, 2019).…”
Section: Proses Pengembangan Perangkatunclassified
“…Strategi digunakan antara lain penugasan, pengarahan, pembiasaan, panutan dan pengkondisian lingkungan akan melekat pada diri anak melalui pengamatan dan melakukan secara nyata (Cinantya et al, 2019). Apalagi sejak masa pandemi pemulihan pembelajaran karakter akan menjadi satu sisi prioritas dengan rancangan media yang diciptakan guru harus yang inovatif dan kreativitas tinggi (Harnanto, 2022). Guru sebagai salah satu hal yang harus membentuk karakter siswa tidak memiliki nilai-nilai dasar itu harus digunakan dalam konteks karakter multikultural pada peserta didik upaya guru untuk melatih kemandirian anak dimaksimalkan (Banamtuan & Natonis, 2019).…”
Section: Proses Pengembangan Perangkatunclassified
“…Some articles explaining value internalization in group/organization (Ahmadi et al, 2020;Harnanto, 2022;Kusumaningrum & Sulistyaningsih, 2021;Mesterjon et al, 2021;Nursyamsiah, 2014;Sultoni et al, 2018;Tambak et al, 2021). All of the articles revealed that the internalization of values is done through formal education realm from senior high school to university.…”
Section: Introductionmentioning
confidence: 99%
“…Those articles also did not explain the procedure of internalization specifically. Only Mesterjon et al (2021) and Harnanto (2022) articles did explain the internalization model through exploratory study and BMT Garuda and Bupanca Media. Meanwhile, Kusumaningrum and Sulistyaningsih (2021) article discussed more the internalization of Pancasila values in adolescents through digital literacy education program.…”
Section: Introductionmentioning
confidence: 99%
“…Responsibilities to society are felt to be greater than personal interests. Because it is the harmony of the Pancasila family, in realizing this attitude of life, humans are demanded by the five precepts of Pancasila, namely by a sense of belief in One Almighty God, by a sense of humanity, which is just and civilized, by awareness to strengthen Indonesian unity, by an attitude that upholds the people led by wisdom in deliberations/representation and to realize social justice for all Indonesian people (Harnanto, 2022).…”
Section: Introductionmentioning
confidence: 99%